2002
DOI: 10.1590/s0100-84042002000200011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light stress on the growth of the epiphytic orchid Cattleya forbesii Lindl. X Laelia tenebrosa Rolfe

Abstract: -(Effects of light stress on the growth of the epiphytic orchid Cattleya forbesii Lindl. X Laelia tenebrosa Rolfe). Considering the performance of CAM epiphytes under high levels of radiation or in shaded environments, with growth rate proportional to light intensity, the objective of this work was to evaluate the effects of long-term light stress on the growth of a Brazilian epiphytic orchid, Cattleya forbesii Lindl. X Laelia tenebrosa Rolfe. Two groups of plants were used in the first experiment, one under 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
11
1
4
Order By: Relevance
“…Both the leaves and roots of P. amabilis are rich in carbohydrates (soluble and starch) that may allow their re-mobilization under certain culture and propagation conditions. Stancato et al (2002), using pseudobulbs of Cattleya forbessii Lindl. × Laelia tenebrosa Rolf.…”
Section: Discussionmentioning
confidence: 99%
“…Both the leaves and roots of P. amabilis are rich in carbohydrates (soluble and starch) that may allow their re-mobilization under certain culture and propagation conditions. Stancato et al (2002), using pseudobulbs of Cattleya forbessii Lindl. × Laelia tenebrosa Rolf.…”
Section: Discussionmentioning
confidence: 99%
“…PS II damage reflected stress in a leaf of plant (Larcher, 2003). Moreover, growth may decline when placed under low lights (Hassan et al, 2010) while in epiphytic orchid plants, growth was decline due to photoinhibition (Stancato et al, 2002). In relation to this, it was suggested that chlorophyll fluorescence could detect the effect stress then followed by physical symptom of the deterioration on plants (Naumann et al, 2008;Percival and Sheriffs, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll fluorescence technique was also reported as a good indicator in determining the stress response. Moreover, extremely excessive light received by plants possibly will damage photosynthetic pigments and structure of plants thykaloid which leads to photodamage (Larcher, 2003) and definitely occurrence of photoinhibition (Stancato et al, 2002). From this, it is vital to know that such exposure to extreme condition as they were subjected to light stress would affect the epiphytic ferns of P. bifurcatum in terms of their physiological attributes.…”
Section: Introductionmentioning
confidence: 99%
“…and other orchid's species commonly grow under open shade area. From the result know that light intensity interfered with growth and development of these orchids (Stancato et al 2002). Table 7.…”
Section: Sunlight Intensitymentioning
confidence: 97%